2004
DOI: 10.1017/s0021859605004879
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition, intake, plasma metabolites, reproductive and metabolic hormones during pregnancy in goats under semi-arid grazing conditions

Abstract: The objective of the study was to determine the chemical composition of the diet, intake and plasma concentrations of glucose, urea and non-esterified fatty acids (NEFA) during pregnancy in goats grazing a thorn scrubland of the semi-arid region of North Mexico. Additionally, monthly changes during pregnancy of plasma concentrations of luteinizing hormone (LH), growth hormone (GH), insulin (INS) and progesterone (P4) were also measured. A herd of 250 goats was bred in August and blood samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Comparing the values obtained in this study with those published for goats in the same type of landscape (Juá rez- Reyes et al, 2004 and2008), it seems clear that goats managed to select the most nutritious plant parts and plant speciesduring the dry period in order to maximize the ingestion of protein.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Comparing the values obtained in this study with those published for goats in the same type of landscape (Juá rez- Reyes et al, 2004 and2008), it seems clear that goats managed to select the most nutritious plant parts and plant speciesduring the dry period in order to maximize the ingestion of protein.…”
Section: Discussionsupporting
confidence: 59%
“…Considering that the average DM intake of adult pregnant mixed breed grazing goats in this landscape in winter is 1.2 kg per goat per day (Juá rez- Reyes et al, 2004;Cerrillo et al, 2006), the levels of this nutrient in the pregnant goats did not meet late pregnancy requirements (National Research Council (NRC), 2007, based on high physical activity). Thus, it seems that, in this particular environment, pregnant goats that carried their fetuses to term handled ingestion of enough high-quality forage to barely maintain a nutritional status to sustain their fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study (Juárez-Reyes et al 2004) that examined the effects of semi-arid grazing conditions on metabolic changes in pregnant goats, a negative correlation was determined between serum insulin and GH levels during advanced pregnancy (December) period and the highest serum GH levels were reported as 20.2 ng/ml. In another study examining milk production and breast development, the serum GH levels were reported in the pregnant goats as 3.22±0.05, 2.84±0.1 and 2.75±0.22 ng/ml on prenatal 1, 7 and 14th days, respectively (Zhang et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the year, goat diets in the grazing areas are composed of about 82% shrubs, 12% herbaceous plants, and 6% grasses (Ramírez et al, 1991). Previous studies have shown that animals from grazing areas consume an average of 135 g crude protein (CP)/kg dry matter (DM) and 2.1 Mcal/d metabolisable energy (ME) (Cerrillo et al, 2006;Juá rez-Reyes et al, 2004).…”
Section: Location and Grazing Conditionsmentioning
confidence: 99%